2011
DOI: 10.1089/vbz.2010.0050
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Q fever, Florac, Southern France, Spring 2007

Abstract: The observed excess of cases of Q fever in Florac, an area endemic for this infection, in spring 2007 could be explained by an aerial transmission from infectious ovine flocks situated close to the town. All local herd owners were re-educated about the risks and prevention practices for Q fever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…goats and sheep). Infections during rural and urban outbreaks are estimated to occur 5 or even 10 km from these sources [ 32 , 42 – 44 ]. Such broad contamination zones support mounting evidence that wind is an important component of the C. burnetti dispersal kernel [ 22 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…goats and sheep). Infections during rural and urban outbreaks are estimated to occur 5 or even 10 km from these sources [ 32 , 42 – 44 ]. Such broad contamination zones support mounting evidence that wind is an important component of the C. burnetti dispersal kernel [ 22 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results expand on this to show that wind may also facilitate outbreaks from infective animal products. For example, a small outbreak in France was likely caused by aerosol transmission from goat and sheep manure infected with C. burnetii applied to nearby pastures [ 44 ]. This suggests that proximity should not be seen in isolation, as wind speed will interact with geography to influence the spread of infection [ 27 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Q fever outbreaks have occurred in many countries worldwide. Studies on these epidemics mainly used ad hoc investigations (affected area/suspected cases sampling; Bond et al, ; Gilsdorf et al, ; Gyuranecz et al, ; Lyytikäinen et al, ; Medic et al, ; Wallensten et al, ) or classical epidemiological study designs, including cross‐sectional studies (Biggs et al, ; Jorm et al, ; King et al, ; Martinov, ; Porten et al, ) and case–control studies (Manfredi Selvaggi et al, ; O'Connor et al, ; Porten et al, ; Tissot‐Dupont, Torres, Nezri, & Raoult, ) to identify associated risk factors.…”
Section: Synthesis and Conclusionmentioning
confidence: 99%
“…Numerous studies suggested the role of the wind, particularly when either cases without contact with ruminants were observed and/or C. burnetii infections on a nearby farm were detected, but in depth analyses were lacking (Biggs et al, ; Bond et al, ; Brouqui et al, ; Gyuranecz et al, ; Jorm et al, ; King et al, ; Lyytikäinen et al, ; O'Connor et al, ; Tissot‐Dupont et al, ). Tissot‐Dupont, Amadei, Nezri, and Raoult () went into further detail with respect to the effect of wind in relation to a cluster of Q fever cases in France.…”
Section: Synthesis and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation